PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, DAN TOTAL ASSETS TURN OVER TERHADAP RETURN ON ASSETS PADA PT. KALBE FARMA TBK PERIODE 2008 - 2021 - Rudy Pudjut Harianto; Dian Nurhariyanto (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2022)
This research aims to analyze the influence of Current Ratio, Debt to Equity Ratio, Total Assets Turn Over toward of Return On Assets at PT. Kalbe Farma Tbk. Period of 2008 - 2021. Data Analyse method that used in this research are Multiple Linier Regression Analyse (correlation coeficient, determination coeficient, simultaneous test/F test, and partial test/t test). Accumulatively, coeficient correlation (R)= 0,898 so that it can be said that the independent variables toward dependent variable in this research can giving the very strength correlation. Result of determination coefficient (R2)= 0,749 it can be said the independent variables can be explain the dependent variable of equal to 74,9% only. While the rest equal to 25,1% explained by other variable from outside model. The result of significantion test could be explained:(1) Current Ratio variable have negative effect and significant on the Return On Assets variable;(2) Debt to Equity Ratio variable have no effect and significant on the Return On Assets variable; and (3) Total Assets Turn Over variable have positive effect and significant on the Return On Assets variable. The result of simultaneous test could be explained: variables of Current Ratio, Debt to Equity Ratio, and Total Assets Turn Over simultaneously have effect and significant on the Return On Assets variable.